VEGFR-2 Expression in Glioblastoma Multiforme Depends on Inflammatory Tumor Microenvironment - Jana Jaal; Marju Kase; Ave Minajeva; Mikk Saretok; Aidi Adamson; Jelizaveta Junninen; Tõnis Metsaots; Tõnu Jõgi; Madis Joonsalu; Markus Vardja; Toomas Asser (International Journal of Inflammation)
Glioblastoma multiforme (GBM) is one of the most angiogenic tumors. However, antiangiogenic therapy has not shown significant clinical efficacy. The aim of our study was to evaluate the impact of inflammatory tumor microenvironment on the expression of vascular endothelial growth factor receptor 2 (VEGFR-2). Surgically excised primary GBM tissues were histologically examined for overall extent of inflammation (score 1–3). After immunohistochemistry, the tissue expression of ICAM-1 (optical density), the number of VEGFR-2 positive (VEGFR-2+) blood vessels (per microscopic field), and the endothelial staining intensity of VEGFR-2 (score 0–3) were determined. In GBM, the extent of inflammation was 1.9 ± 0.7 (group mean ± SD). Mean optical density of inflammatory mediator ICAM-1 was 57.0 ± 27.1 (pixel values). The number of VEGFR-2+ blood vessels and endothelial VEGFR-2 staining intensity were 6.2 ± 2.4 and 1.2 ± 0.8, respectively. A positive association was found between endothelial VEGFR-2 staining intensity and the extent of inflammation (p=0.005). Moreover, VEGFR-2 staining intensity correlated with the expression level of ICAM-1 (p=0.026). The expression of VEGFR-2, one of the main targets of antiangiogenic therapy, depends on GBM microenvironment. Higher endothelial VEGFR-2 levels were seen in the presence of more pronounced inflammation. Target dependence on inflammatory tumor microenvironment has to be taken into consideration when treatment approaches that block VEGFR-2 signaling are designed.